Cell-surface receptors enable perception of extracellular cytokinins - Antoniadi, Ioanna; Novák, Ondřej; Gelová, Zuzana; Johnson, Alexander; Plíhal, Ondřej; Simerský, Radim; Mik, Václav; Vain, Thomas; Mateo-Bonmatí, Eduardo; Karady, Michal; Pernisová, Markéta; Plačková, Lenka; et al. (Nature communications, 2020)
Cytokinins are mobile multifunctional plant hormones with roles in development and stress resilience. Although their Histidine Kinase receptors are substantially localised to the endoplasmic reticulum, cellular sites of cytokinin perception and importance of spatially heterogeneous cytokinin distribution continue to be debated. Here we show that cytokinin perception by plasma membrane receptors is an effective additional path for cytokinin response. Readout from a Two Component Signalling cytokinin-specific reporter (TCSn::GFP) closely matches intracellular cytokinin content in roots, yet we also find cytokinins in extracellular fluid, potentially enabling action at the cell surface. Cytokinins covalently linked to beads that could not pass the plasma membrane increased expression of both TCSn::GFP and Cytokinin Response Factors. Super-resolution microscopy of GFP-labelled receptors and diminished TCSn::GFP response to immobilised cytokinins in cytokinin receptor mutants, further indicate that receptors can function at the cell surface. We argue that dual intracellular and surface locations may augment flexibility of cytokinin responses.
Keywords: mutace; extracelulární tekutina; Green Fluorescent Proteins; geneticky modifikované rostliny; Arabidopsis Proteins; Adenine; Plants, Genetically Modified; rekombinantní proteiny; Recombinant Proteins; Mutation; signální transdukce; cytokininy; Signal Transduction; Cytokinins; proteiny huseníčku; zelené fluorescenční proteiny; adenin; histidinkinasa; Extracellular Fluid; Arabidopsis; Histidine Kinase